Comprensión lectora de textos científicos y rendimiento escolar en ciencia, tecnología y ambiente en estudiantes de 2do año de secundaria de una institución educativa del Callao - Arroyo Montes, Carlos Javier (2010)
The purpose of the research is to find the relation between the reading comprehension of the scientific texts and the school performance in science technology and environment in students of 2nd year of public high school of Callao’s Region. The sample is formed by 94 students of both sexes; they were evaluated across the test applied in the International Program of Students' Evaluation constituted by six fragments of scientific texts in the science area. The sample type is no probabilistic of correlational design. Finally, the results allow demostrate the teacher’s labor for initiating to the students in the field of the investigation and the usefulness of the scientific texts to the process of education learning.